Recent studies on applications of aquatic weed plants in phytoremediation of wastewater: A review article - Mustafa H.M.; Hayder G. (Ain Shams University, 2023)
Agricultural robots; Agriculture; Biochemistry; Bioremediation; Groundwater; Heavy metals; Industrial water treatment; Population statistics; Wastewater treatment; Water pollution; Bioaccumulation potential; Conventional treatments; Industrial development; Industrial wastewaters; Recent researches; Toxic environments; Wastewater remediation; Water contaminants; Sewage treatment plants